Functionalization of polymer particles for additive manufacturing processes by plasma treatment in a fluidized bed reactor - Sachs, Marius; Schmidt, Jochen; Peukert, Wolfgang; Wirth, Karl-Ernst (8th International Conference for Conveying and Handling of Particulate Solids, CHoPS 2015, 2015)
Recently additive manufacturing processes such as laser beam melting (LBM) of polymers have gained more importance for industrial applications [1]. Tailor-made modification of polymers is essential in order to make these processes more efficient and to cover the industrial demands. The so far used polymer materials show weak performance regarding the mechanical stability of processed parts. To overcome this limitation, a new route to functionalize the surface of commercially available polymer particles (PA12) using an atmospheric plasma jet in combination with a fluidized bed reactor (FBR) has been investigated. Consequently, an improvement of adhesion and wettability [2] of the polymer surface without restraining the bulk properties of the powder is achieved. The atmospheric plasma jet process can provide reactive species at moderate temperatures which are suitable for polymer material. The functionalization of the polymer powders improves the quality of the devices build in a LBM-proces
Keywords: additive; manufacturing; polymer; tailor-made; functionalization; stability